Human prion diseases - Pocchiari, Maurizio; Manson, Jean C. (Handbook of clinical neurology, 2018)
Human Prion Diseases, Volume 153 is designed to update the reader on the latest advances and clinical aspects of prion diseases. The book is organized into five sections, including the pathophysiology of prions and a description of animal and human diseases. This is followed by detailed reports on recent advances in diagnosis strategies for the development of novel anti-prion molecules and possible designs of clinical trials in such a rare disease. An introductory chapter gives an extensive historical background of prion research, with a final chapter highlighting recent progress, and more importantly, unsolved problems"--Publisher's description